Circular Economy in Morocco: Status and Perspectives and Policy Implications for Vietnam - Van, Truong Hoang Thuy (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
This paper explores the current status of the circular economy (CE) in Morocco, its potential future directions, and policy implications for Vietnam. The concept of CE, which promotes sustainable resource use, waste reduction, and regeneration, is increasingly gaining global traction. Morocco, having made significant progress in sectors such as waste management, agriculture, renewable energy, and water resource management, serves as a valuable case study. Key initiatives like the National Solid Waste Management Program (PNDM) and the "Green Morocco Plan" highlight Morocco’s successful integration of CE principles. Despite challenges such as financial constraints and low public awareness, Morocco's transition to a circular economy presents numerous opportunities, including job creation and innovation. For Vietnam, which faces growing environmental and resource pressures, Morocco’s experience offers critical insights. By adopting CE principles in waste management, agriculture, renewable energy, and water management, Vietnam can move toward more sustainable development. The paper suggests specific policy recommendations, including fostering public-private partnerships, enhancing regulatory frameworks, and promoting green financing. The lessons drawn from Morocco’s journey can help Vietnam align its growth with environmental sustainability, positioning both countries as leaders in the global shift towards a circular economy.